Plasmatic and Platelet Anti-Plasmins and Anti-Activators - den Ottolander, G. J. H; Leijnse, B; Cremer-Elfrink, M. J. H (Thrombosis and Haemostasis, 1969)
The values for plasmatic and thrombocytic anti-plasmin and anti-UK were determined in normal test persons and in 107 patients with different diseases.In 12 patients with a fresh venous thrombosis the values of these inhibitors were within normal limits.In 6 patients with liver cirrhosis no significantly lowered values were found.Also in patients with different haematological diseases no abnormality was found. A relationship between plasmatic and thrombocytic anti-UK was found.